Tofu Product Branding for Culinary Tourism of Sumedang, Indonesia - Dasrun Hidayat; Hanny Hafiar; Anisti Anisti (Universitas Muhammadiyah Yogyakarta, 2019)
Measuring standards for the management of tofu products as culinary tourism can contribute to the branding of the city of Sumedang, Indonesia. With the challenges in the technology era 4.0 the culinary industry, including Sumedang, is demanded to do branding through digital technology. This is the background of the importance of this study. The research design uses the ethnographic study of public relations with a qualitative approach. Data collection involved 4 producers and 4 consumers through interview and observation techniques. This research found differentiation as a strategy for managing tofu products. The differentiation strategy includes the use of digital promotional media in the form of websites and social media, which previously only used conventional media, such as banners. Differentiation can also be found in packaging using boxes made of woven bamboo. Another differentiation is in the variation of flavors by adding sambal kecap (chili soy sauce), sambal oncom (chili sauce mixed with a fermented caked product made of peanut press cake), sambal hejo (green chili sauce) in addition to its original accompaniment of the whole chilies. However, these changes do not change the tofu price of around 500 rupiahs per piece. Differentiation as an effort to build the branding of Sumedang city is what drives the local government to make tofu products as culinary tourism. This study offers a concept of culinary tourism as cultural tourism in the city of Sumedang. The concept of this tourism has not been much researched, although culinary culture is one of the intellectual properties that must be developed. Product development through product differentiation and convergence of Internet-based media is a product communication strategy effort for managing Sumedang Tofu products.